Interleukin‐1 blockade treatment decreasing cardiovascular risk - Zheng, Zi‐Heng; Zeng, Xun; Nie, Xiao‐Ying; Cheng, Yun‐Jiu; Liu, Jun; Lin, Xiao‐Xiong; Yao, Hao; Ji, Cheng‐Cheng; Chen, Xu‐Miao; Jun, Fan; Wu, Su‐Hua (Clinical cardiology (Mahwah, N.J.), 2019)
Background Interleukin‐1 (IL‐1) played a role in the occurrence and development of atherosclerosis and cardiovascular events. However, the association between IL‐1 blockage treatment and reducing of cardiovascular risk remains poorly defined. Hypothesis IL‐1 blockage treatment reduce the risk and incidence rate of overall major adverse cardiovascular events (MACE), all‐cause death, acute myocardial infarction(MI), unstable angina and heart failure. Methods We performed a search of published reports by using MEDLINE database (January 1, 2005 to April 1, 2018). The randomized controlled trials (RCTs) that reported sample size and occurrence numbers in test group and placebo group for the associations of interest were included. Results Eight RCT studies involving 15 647 participants were identified. Compared with those who took no IL‐1 blockage, patients taking IL‐1 blockage experienced a decreased risk of overall MACE (RR 0.88, 95% CI 0.82‐0.94), unstable angina (RR 0.80, 95% CI 0.66‐0.98), and breakthrough or recurrence of heart failure (RR 0.44, 95% CI 0.22‐0.87). No association was found between IL‐1 blockage treatment and death from all cause (RR 0.91, 95% CI 0.83‐1.00) as well as acute MI (RR 0.85, 95% CI 0.71‐1.01). The RRs associated with overall MACE, death from all cause, acute MI, and unstable angina for anakinra were 1.05, 1.16, 2.97, and 0.56, respectively, and for canakinumab were 1.05, 0.91, 0.80, and 0.80, respectively. Conclusions Administration of IL‐1 blockage was associated with decrease risks of overall MACE, unstable angina, and breakthrough or recurrence of heart failure, but not with death from all cause as well as acute MI.